Factors affecting the attraction of Chinese foreign direct investment - CHANTHAVONG, Souliyadeth; SOMSAMONE , Vilayphone; SIPHADA, Vaththanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
In this research, using secondary data for the years 1991 - 2021, we analyze factors that influence the attraction of Chinese foreign direct investment. The relationship between independent factors and dependent variables has been examined utilizing multi-regression based on the vector auto regression (VAR) model approach. Chinese’s Foreign direct investment is regarded as a dependent variable. Trade Openness, inflation, GDP per capita and exchange rates have all been taken into account as independent variables. The Granger Causality test found that China's direct investment has a bi-way causality relationship with trade openness and inflation. China's direct investment has a unidirectional causality relationship with GDP per capita. but China's direct investment has no causal relationship with the exchange rate. The results of the VAR model test found that China's per capita income and direct investment have a relationship in the same direction with a level of statistical significance of 0.1. It means that GDP per capita changes by 1% will result in China's direct investment increasing by 1.05%, While inflation rate and China's direct investment have a relationship in the opposite direction with a statistical significance level of 0.1. If the inflation rate changes by 1%, it will result in China's direct investment decreasing by 0.35%. Trade openness and exchange rate are related to China's direct investment in the opposite direction and the same direction, respectively, but there is no statistical significance. The Impulse Response Function test shows that each variable changes in the shock state in the initial phase is quite intense with increases and decreases with each period. Over time, it gradually adjusts down, then can be adjusted to a long-term balanced focus. Finally, the variance decomposition test found that all variables have more of their own variance than other variables, China's direct investment has an average of 73.03% of its own variance and over time, China's direct investment has been affected by other variables, and the effect of itself has started to decrease and can reach a balance point around the 8th year.